Impact of a rock avalanche on a moraine-dammed proglacial lake: Laguna Safuna Alta, Cordillera Blanca, Peru - Hubbard, Bryn (2005)
Original abstract: Moraines that dam proglacial lakes pose an increasing hazard to communities in the Andes and other mountain ranges. The moraines are prone to failure through collapse, overtopping by lake waters or the effect of displacement waves resulting from ice and rock avalanches. Resulting floods have led to the loss of thousands of lives in the Cordillera Blanca mountains of Peru alone in the last 100 years. On 22 April 2002 a rock avalanche occurred immediately to the south-west of Laguna Safuna Alta, in the Cordillera Blanca. The geomorphic evidence for the nature, magnitude and consequences of this event was investigated in August 2002. Field mapping indicated that the avalanche deposited 8–20 × 106 m3 of rock into the lake and onto the surface of the frontal region of Glaciar Pucajirca, which flows into the lake. Repeated bathymetric surveying indicated that ~5 × 106 m3 of this material was deposited directly into the lake. The immediate effect of this event was to create a displacement wave that gained in height as it travelled along the lake basin, overtopping the impounding moraine at the lake’s northern end. To achieve overtopping, the maximum wave height must have been greater than 100 m. This, and subsequent seiche waves, caused extensive erosion of both the proximal and distal faces of the impounding terminal moraine. Further deep gullying of the distal face of this moraine resulted from the supply of pressurized water to the face via a relief overflow tunnel constructed in 1978. Two-dimensional, steady-state analysis of the stability of the post-avalanche moraine rampart indicates that its proximal face remains susceptible to major large-scale rotational failure.